Process tensor approaches to modeling two-dimensional spectroscopy - Roosmarijn de Wit; Jonathan Keeling; Brendon W. Lovett; Alex W. Chin (Physical Review Research)
Problems in the field of open quantum systems often involve an environment that strongly influences the dynamics of excited states. Here we present a numerical method to model optical spectra of non-Markovian open quantum systems. The method employs a process tensor framework to efficiently compute multitime correlations in a numerically exact way. To demonstrate the efficacy of our method, we compare 2D electronic spectroscopy simulations produced through our method to Markovian master equation simulations in three different system-bath coupling regimes.